Interactive Websites in Physics Education: A Bibliometric Analysis and Trends Review - Marwanti, Kissi; Wibowo, Firmanul Catur; Nasbey, Hadi (Jurnal Ilmiah Pendidikan Fisika, 2024)
This study examines the trend and contribution of interactive websites in physics education through bibliometric analysis. Using R Bibliometrix, 38 articles from 1999 to 2024 were analyzed in annual scientific production, country scientific production, most cited countries, most cited documents globally, and word clouds. The types of documents obtained from the Scopus database in the form of articles, book chapters, conference papers, and conference reviews. The findings of the analysis show that the key trends include students, websites, e-learning, education, and teaching. While gaps remain in interactive learning tools, learning experiences, learning management systems, learning processes, and differentiation. This study could serve as a global guide for researchers and educators creating interactive physics learning websites.